Analysis Of Herding Behavior And Capital Structure In Non-Financial Companies In Asean-5 That Issue Sustainability Reports And Its Impact On Company Performance - Swastika, Gema Mia (Journal Research of Social Science, Economics, and Management, 2023)
This research was conducted with the aim of knowing whether or not there is herding behavior seen from the value of the debt to equity ratio, the effect of sustainability reports on firm performance and determining which company leaders or followers are better in firm performance. The herding behavior observed in this study was between companies in five countries. The total number of companies is 127 companies are Indonesia, Malaysia, Singapore, Thailand and the Philippines with an observation period of 2018 to 2022. To measure sustainability report disclosure, a checklist is made based on the suitability of the disclosures with 91 indicators. Firm performance is proxied by Tobin's Q, return on assets and net profit margin, while the controls in this study are proxied by total assets and firm age. The analytical method used in this study is by measuring the herding manager index and the SEM - PLS method using the WARP PLS application version 7.0. From the test results it was found that there was herding capital structure in the five observation countries, disclosure of sustainability reports had a positive effect on return on assets and Tobin's Q. Meanwhile, disclosure of sustainability reports had no effect on net profit margin. Then from the test results it is proven that the leader company is better than the follower company in firm performance.